Shadow of the Dinosaurs - Nolan, Dennis, 1945- (New York : Simon & Schuster Books for Young Readers, 2001)
A boy and his dog find a magic dinosaur bone that shows them what life was like among the dinosaurs.
Accelerated Reader AR